Optimasi Perawatan Pasien Rawat Inap Berbasis Android Untuk Pemantauan Cairan Infus - Sumarno Sumarno; Arief Wisaksono; Mochammad Luthfan Hakim; Riski Yulianto; Hindarto Hindarto (Universitas Budi Darma, 2023)
Good and thorough patient care at the hospital is very necessary, so that someone who is treated at the hospital can be served properly, one of which is giving infusions to patients. So far, many hospitals or puskesmas provide infusions manually, relying on nurses or those who look after the patient. This study aims to provide Android-based infusion fluids, so that nurses or caregivers can find out the condition of the patient's infusion. The research used is quantitative research with experimental methods. The location of the research was carried out at the Siti Suaibah clinic located in Tempel Village, Kec.Krian, Kab.Sidoarjo. Data processing methods are used to sort data according to the topic where the data produces something from a research and also Coding data. The research carried out consisted of two stages, the first was making software and the second was making hardware. The results of the research are sending infusion fluid data every 10-12 seconds, and auto refreshing on the blynk application every 5 seconds with a measurement error percentage of 2.15 from the results of manual measurements as well as sending notifications on smartphones if the volume of intravenous fluids is below 6 mm by 70 time. The data sharing process was successful because the data held by the ultrasonic and Mlx90614 temperature of the infusion fluid were successfully stored in the Blynk database via the Arduino Wemos D1R2.